Les chiites et la célébration du gamou au Sénégal - Macoumba Diop (Revue des Mondes Musulmans et de la Méditerranée)
Since the 2000s, Shiites in Senegal have been taking part in the celebration of the birth of the Prophet. Although they follow the Sufi brotherhood’s tradition of celebrating the Mawlid, known as gamou in Senegal, the Shiites consider that this festival should be celebrated in a different way. The first part of this article reviews the elements that make the gamou a major event in the religious, social and even political life of Senegal. I then show how the celebration of this festival by Senegalese Shiites reflects both a desire to draw closer to Sufi brotherhoods, notably in a common opposition to Wahhabi attacks, and a desire to distinguish themselves from the Sunni religious environment.